O disseleneto de difenila protege o modelo Caenorhabditis elegans para a doença de huntington através da ativação antioxidantes reduzindo a agregação de proteínas - Baptista, Fabiane Bicca Obetine (2020)
Huntington's disease (HD) is a progressive, autosomal dominant neurodegenerative disease with a distinct phenotype, including chorea and dystonia, incoordination, cognitive decline and behavioral difficulties. Characterized by the presence of the mutant huntingtin protein, which results from an expanded CAG repeat, leading to a variable length polyglutamine (Poli-Q) chain at the N-terminal. Most neurodegenerative diseases are characterized by abnormal deposition and consequent protein aggregation, which impair the dynamics of protein networks and result in the imbalance of cellular homeostasis. In this work, we used the Caenorhabditis elegans experimental model due to its easy manipulation and high homology of genes and signaling pathways in relation to mammals. The worms were exposed to diphenyl diselenide (PhSe)2 at concentrations of 25, 50 and 100 μM, from young adults and analyzed for poly-Q aggregation and neuronal and muscle viability. Based on the theory of aging and the aggregation of proteins related to HD, and taking into account that (PhSe)2 has antioxidant activity, then we will analyze some possible pathways involved related to HD), we will also analyze as to its potential in increasing the quality and life span of C. elegans.